Drug treatment of scrub typhus - Rajapakse, Senaka; Rodrigo, Chaturaka; Fernando, Sumadhya Deepika (SAGE Publications, 2011)
Scrub typhus is a vector-borne disease caused by the pathogen Orientia tsutsugamushi. We review the published literature for evidence on drug treatment in scrub typhus. Doxycycline has a proven efficacy in several trials and a meta-analysis, although resistance has been documented in parts of northern Thailand. Macrolides are equally efficacious and have less adverse effects, but they are expensive. Azithromycin is the recommended drug in pregnancy and for children. Rifampicin is effective in areas where doxycycline resistance is present. Quinolones have shown some degree of efficacy but the evidence is scant. Most clinical evidence on drug treatment is from cases of mild-to-moderate scrub typhus. Further study is needed on the efficacy of different antibiotics in the treatment of severe, lifethreatening scrub typhus